Analysis of humidity sensitivity of silicon strip sensors for ATLAS upgrade tracker, pre- and post-irradiation. (1st February 2023) - Fernández-Tejero, J.; Affolder, A.; Bach, E.; Basso, M.J.; Bhardwaj, A.; Cindro, V.; Dowling, A.; Fadeyev, V.; Fleta, C.; Fournier, A.; Hara, K.; Howe, A.; et al.
Abstract: During the prototyping phase of the new ATLAS Inner-Tracker (ITk) strip sensors, a degradation of the device breakdown voltage at high humidity was observed. Although the degradation was temporary, showing a fast recovery in dry conditions, the study of the influence of humidity on the sensor performance was critical to establish counter-measures and handling protocols during production testing in order to ensure the proper performance of the upgraded detector. The work presented here has the objective to study for the first time the breakdown voltage deterioration in presence of ambient humidity of ATLAS ITk production-layout strip sensors with different surface properties, before and after proton, neutron and gamma irradiations. A study of the humidity sensitivity of miniature ATLAS ITk strip sensors, before and after proton irradiations, is also presented to compare the sensitivity of devices with different sizes. The sensors were also exposed for several days to high humidity with the aim to recreate and evaluate the influence of the detector integration environment expected during the Large Hadron Collider (LHC) Long Shutdown 3 (LS3) in 2026, where the sensors will be exposed to ambient humidity for prolonged times.